Harmonizing the Rules: “A Socio-Legal Analysis of FIFA Stadium Safety and Security Standards and Indonesian Football Regulations – Aftermath Kanjuruhan Tragedy" - Utama, Kartika Widya; Putrijanti, Aju; Sukmadewi, Yudhitiya Dyah; Apriliani, Lydia (LAW REFORM, 2024)
The death of over 100 Indonesian football supporters at Kanjuruhan Stadium has raised significant concerns about the legal aspects of security and safety management in Indonesian stadiums. This conceptual article conducts a comparative legal analysis between FIFA's Stadium Safety and Security Regulations and the PSSI Safety and Security Regulation 2021, exploring potential avenues for harmonization. With a focus on ensuring the safety of spectators, players, and officials, the study examines the nuanced differences and commonalities between these regulatory frameworks. By identifying areas of convergence, the article aims to contribute to a more unified approach in addressing critical aspects of stadium safety and security within Indonesian football culture, particularly regarding the presence of police officers. Through this socio-legal approach, the article seeks to stimulate discourse on necessary adjustments and reforms to align domestic regulations with FIFA standards, fostering a safe and standardized environment for football enthusiasts in Indonesia. The findings of the article indicate a shift in principles in the management of football matches within PSSI. Regulations that should serve as a reference for upholding the principles of safety and security for all parties involved in a football match have shifted towards becoming regulations designed to avoid responsibility.